PELUANG PENGEMBANGAN POTENSI TEBING MANDU SEBAGAI KAWASAN GEOPARK DI KECAMATAN ANGGERAJA KABUAPTEN ENREKANG - Hervina, Hervina; Arfandi, Arfandi (xxxx-xxxx, 2024)
Anggeraja is one of the sub-districts in Enrekang Regency, South Sulawesi with the sub-district capital being Cakke. Anggeraja District consists of 12 villages and 3 sub-districts, one of which is Tanete sub-district. One of the environments in Tanete Village which is the focus of the research is the Spectacle Environment where there is the Mandu Cliff. Astronomically, this cliff is located at  119 48’ 24.98” East Longitude and 3 25’ 10.79” South Latitude. The Mandu Cliffs show tourism potential which has the opportunity to become a Geological Park (Geopark). However, unfortunately the Mandu Cliffs tourist attraction has recently been neglected and neglected. This research is a type of qualitative research with a descriptive approach. Data collection techniques in this research are observation, interviews and documentation. The analysis used is Miles & Huberman. The aim of this research is to determine the tourism potential of the Mandu Cliffs and to determine the opportunities for the Mandu Cliffs to become a Geopark area.